Associations of midpoint of sleep and night sleep duration with type 2 diabetes mellitus in Chinese rural population: the Henan rural cohort study - Zhihan Zhai; Xiaotian Liu; Haiqing Zhang; Xiaokang Dong; Yaling He; Miaomiao Niu; Mingming Pan; Chongjian Wang; Xiaoqiong Wang; Yuqian Li (BMC, 2021)
Abstract Background The study aimed to investigate the independent and combined effects of midpoint of sleep and night sleep duration on type 2 diabetes mellitus (T2DM) in areas with limited resources. Methods A total of 37,276 participants (14,456 men and 22,820 women) were derived from the Henan Rural Cohort Study. Sleep information was assessed based on the Pittsburgh Sleep Quality Index. Logistic regression models and restricted cubic splines were used to estimate the relationship of the midpoint of sleep and night sleep duration with T2DM. Results Of the 37,276 included participants, 3580 subjects suffered from T2DM. The mean midpoint of sleep among the Early, Intermediate and Late groups were 1:05 AM ±23 min, 1:56 AM ±14 min, and 2:57 AM ±34 min, respectively. Compared to the Intermediate group, adjusted odds ratios (ORs) and 95% confidence interval (CI) of T2DM were 1.13 (1.04-1.22) and 1.14 (1.03-1.26) in the Early group and the Late group. Adjusted OR (95% CI) for T2DM compared with the reference (7- h) was 1.28 (1.08-1.51) for longer (≥ 10 h) night sleep duration. The combination of late midpoint of sleep and night sleep duration (≥ 9 h) increased 38% (95% CI 10-74%) prevalence of T2DM. These associations were more obvious in women than men. Conclusions Late and early midpoint of sleep and long night sleep duration were all associated with higher prevalence of T2DM. Meanwhile, midpoint of sleep and night sleep duration might have combined effects on the prevalence of T2DM, which provided potential health implications for T2DM prevention, especially in rural women. Trial registration The Henan Rural Cohort Study has been registered at Chinese Clinical Trial Register (Registration number: ChiCTR-OOC-15006699 ). Date of registration: 2015-07-06.